Students’ Perspectives on the Use of Chat-GPT in the Fields of Phonology, Morphology, and Syntactics in Arabic Language Learning - Ahmada Rahmaddani; Naifah (Journal of Islamic Education Thought and Development, 2025)
This study aims to explore the use of ChatGPT in learning Arabic phonology, morphology, and syntax from the perspective of students of the Arabic Language Education (PBA) Study Programme. Using a qualitative approach with a literature review method, this research analyses data from various academic sources. The results show that ChatGPT is effective in helping students understand linguistic aspects of Arabic, such as pronunciation of hijaiyah letters, word derivation, and i'rab analysis. The technology improves learning efficiency by providing instant, interactive and adaptive answers to students' needs, saving time and money. However, challenges such as limited understanding of cultural context and potential technical errors if questions are not specific remain. Therefore, ChatGPT should be used as an additional tool, not a replacement for traditional methods. This research shows that ChatGPT integration can create a more innovative and personalised learning experience, but it must be implemented carefully